2017
DOI: 10.6007/ijarped/v6-i3/3081
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy and Academic Performance of Secondary Schools Students in Perak: An Exploratory Outlook

Abstract: Self-efficacy is an important entity in elevating someone to a better level. Without efficacy, individuals will not be able to face difficulties in life. In the context of secondary school students in Perak, there were different perspectives on self-efficacy between male and female students. Female students were more optimistic when facing difficulties in their studies compared to male students. This may be due to the nature of gender itself. They were inherently easier in putting trust to a certain degree hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Their study involved a sample of 169 adolescent students aged 17-19 years; and the findings revealed that most respondents scored a high mean of self-efficacy in social behaviour and emotions within and across academic achievement levels, and were academic achievers. Furthermore, the findings corroborate what Suraya and Yunus (2017) found out regarding secondary school students' self-efficacy and academic performance. The study involved a sample of 588 respondents; and among them males were 233 and females were 355.…”
Section: Level Of Self-efficacy Among Adolescent Students In Public S...supporting
confidence: 89%
“…Their study involved a sample of 169 adolescent students aged 17-19 years; and the findings revealed that most respondents scored a high mean of self-efficacy in social behaviour and emotions within and across academic achievement levels, and were academic achievers. Furthermore, the findings corroborate what Suraya and Yunus (2017) found out regarding secondary school students' self-efficacy and academic performance. The study involved a sample of 588 respondents; and among them males were 233 and females were 355.…”
Section: Level Of Self-efficacy Among Adolescent Students In Public S...supporting
confidence: 89%
“…Several studies have demonstrated the positive impact of self-efficacy on various factors, particularly students' academic abilities and performance. Mohamed and Yunus (2017) reported that individuals with high perceived self-efficacy are inclined to attempt more tasks and persevere with them longer than individuals with low perceived self-efficacy. This inclination is rooted in the belief that those with higher self-efficacy feel greater control over their surroundings and the events that occur, whereas individuals with lower self-efficacy often experience event-related anxiety and a lack of environmental control.…”
Section: Self-efficacymentioning
confidence: 99%
“…It is because teachers' performance can be seen from the students' achievement (Széll, 2013). Another study that proves selfefficacy positively influences teachers' performance is also conducted by Mohamed & Yunus (2017).…”
Section: Hypothesis Testingmentioning
confidence: 99%